ChemInform Abstract: Asymmetric Construction of Quaternary Stereogenic Centers via Auxiliary‐Based SN2′ Reactions: A Case of 1, 7‐Relative Stereogenesis. Issue 21 (27th May 2014) - Denmark, Scott E.; Marble, Lyndon K.
Abstract Reactions of carbamates [(I), (VII), and (IX)] with phenyl‐ or butylcopper afford alkenes containing quaternary centers with modest to high enantiomeric excess.